Embedded System Simulation Using Renode - Ferenc Speiser; István Szalay; Dénes Fodor (Engineering Proceedings, 2024)
In the automotive industry, the reduction of development costs is of key importance. The development of electrical hardware is an expensive, time-consuming process with a lot of development stages (e.g., prototyping, electrical testing, mechanical testing, lifecycle testing). There is a growing need to increase the cost-effectiveness of the development and testing phases of embedded software using virtualization. Using this method, less prototype manufacturing is necessary since the simulations allow for faster and more effective discovery of a large portion of possible faults without building a hardware prototype. Renode is an open source embedded system simulation framework that facilitates software-based testing. The main goal of this paper is to explore the usability of the framework for automotive applications.